THE IMPORTANCE OF ASSESSING THE LEVEL OF PHYSICAL FITNESS, ORGANIZATION AND QUALITY OF NUTRITION OF CHILDREN (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In the republic, great attention is paid to the state of health of the younger generation. Particular importance is attached to expanding the network of preschool institutions [1] and improving conditions in them for comprehensive physical, intellectual and aesthetic development of children. Children's physical fitness is determined by the level of development of physical qualities and motor skills. Daily rational and balanced nutrition is also important for children's health [2]. Insufficient or excessive nutrition can lead to disease, disorders in the growth and development of the child's body. Studies by a number of authors have established that the nutrition of children can be irregular, irrational and unbalanced. Environmental factors, socio-economic status of the family and parents' education play a significant role in the formation of children's lifestyle, including motor activity and nutrition [3,4]. In view of the above, an important step is to educate parents on the basics of healthy nutrition and physical activity. Conducting seminars and workshops in preschool institutions will help raise awareness among families about the importance of proper nutrition and regular physical activity for children's health. This, in turn, will contribute to the formation of sustainable habits in the younger generation that will last throughout life.